2012
DOI: 10.3415/vcot-11-12-0175
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complications and short-term outcome after unilateral or single-session bilateral tibial tuberosity advancement for cranial cruciate rupture in dogs

Abstract: This is the first report evaluating the use of bilateral simultaneous TTA. There was no significant difference in complication rates between unilateral and bilateral single-session TTA. Additional evaluation is needed to fully determine the extent of complications and long-term outcome of bilateral single-session TTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 27 publications
6
52
0
2
Order By: Relevance
“…Simultaneous bilateral TTA procedures and concurrent correction of patellar luxation via tibial tuberosity transposition advancement (TTTA) are other factors that could be expected to increase the risk of postoperative complication. Hirshenson et al found no difference in complication rates after unilateral (11.7%) or single‐session bilateral TTA (17.6%) . Yeadon et al reported complication in 18% of dogs undergoing TTTA, which is within the range of major complication proportions in previous reports (12‐21%) …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Simultaneous bilateral TTA procedures and concurrent correction of patellar luxation via tibial tuberosity transposition advancement (TTTA) are other factors that could be expected to increase the risk of postoperative complication. Hirshenson et al found no difference in complication rates after unilateral (11.7%) or single‐session bilateral TTA (17.6%) . Yeadon et al reported complication in 18% of dogs undergoing TTTA, which is within the range of major complication proportions in previous reports (12‐21%) …”
Section: Introductionmentioning
confidence: 75%
“…Postoperative SSI is a concern in any orthopedic procedure requiring placement of implants because of the potential biofilm formation and associated bacterial resistance . SSI has been reported in 0.5‐5.3% of TTAs . The highest incidence was reported in a study of 224 TTAs, where prolonged surgery times directly increased the risk of infection, and postoperative antibiotherapy did not prevent SSI .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of fracture with the original TTA is reported as 1%‐4.3% . However, these were postoperative fractures as the complete osteotomy performed in the original TTA obviates intraoperative fracture beyond surgeon error (eg, misplacement of the fork or screws).…”
Section: Discussionmentioning
confidence: 99%
“…Tal fato associado ao trauma assistido infere a ocorrência da fratura por sobrecarga na região ainda não cicatrizada. Embora muitas complicações pós-operatórias nas TTAs venham a aparecer devido a erros de técnica cirúrgica (HIRSHENSON et al, 2012), neste caso a técnica estava aparentemente correta (SLOCUM; SLOCUM, 1993).…”
Section: Discussionunclassified
“…Hirshenson et al (2012) tiveram dois casos de fratura da crista tibial a longo prazo, não sendo necessária nova intervenção cirúrgica devido à ausência de sintomatologia clínica. Neste relato de caso, optou-se pela revisão cirúrgica da fratura devido à severidade dos sinais clínicos apresentadas pelo paciente.…”
Section: Discussionunclassified